Urban tree relating to urban infrastructure in Almenara, MG, Brazil (Terr@ Plural, 2020)
Afforestation promotes environmental benefits, but a lack of planning can promote urban conflicts. This research evaluated afforestation and diagnosed the possible conflicts between trees and urban infrastructure in eight neighborhoods of Almenara, MG. Conflicts with the power grid, building, and the traffic of people and vehicles were identified. There were 2,038 trees belonging to 61 species, 61% exotic. The most uncomfortable situations for urban mobility were trees positioned on the street bed (56%), sidewalks with a width of less than 1.90 m (74%), and an average height of the first fork below 1.80 m, among others. It was observed that the population needs guidance regarding their participation in the management of the city's trees. Thus, this diagnosis may help support the review of the city's Master Plan and the creation of a future urban afforestation management plan in the municipality.
Keywords: Urbanization; afforestation; mobility; urban planning